1995
DOI: 10.1038/bjc.1995.521
|View full text |Cite
|
Sign up to set email alerts
|

Pressure tuning infrared spectroscopic study of cisplatin-induced structural changes in a phosphatidylserine model membrane

Abstract: Summary The dynamic effect of cis-diamminedichloroplatinum(II) (DPP) and its aquated metabolite (DDP-OH) on a dimyristoylphosphatidylserine (DMPS) model membrane was investigated by pressure tuning vibrational spectroscopy. The native species (DDP-C1) and the aquated species (DPP-OH) were both observed to bind to the carboxylate group of the serine as evidenced by a frequency shift of 1622-1620 cm '. However, only DDP-OH was observed to bind to the phosphate group (PO2-). The binding of either drug to DMPS re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 33 publications
(31 reference statements)
1
11
0
Order By: Relevance
“…First, in patients, cisplatin elicits a range of short-term secondary effects that include disturbance of the hydroelectrolytic balance, gastrointestinal troubles, hearing alterations, imbalance, and modified perceptions or sensations. Second, in cellular models, cisplatin acts on microtubules (4) and actin polymerization (5) and can modify or interact with phospholipids (6,7). Other studies including genetic screens for cisplatin resistance have documented that membrane proteins (8), enzymes involved in lipid synthesis and modification (9), or cellular enzymes (10) are affected by this drug.…”
Section: Introductionmentioning
confidence: 99%
“…First, in patients, cisplatin elicits a range of short-term secondary effects that include disturbance of the hydroelectrolytic balance, gastrointestinal troubles, hearing alterations, imbalance, and modified perceptions or sensations. Second, in cellular models, cisplatin acts on microtubules (4) and actin polymerization (5) and can modify or interact with phospholipids (6,7). Other studies including genetic screens for cisplatin resistance have documented that membrane proteins (8), enzymes involved in lipid synthesis and modification (9), or cellular enzymes (10) are affected by this drug.…”
Section: Introductionmentioning
confidence: 99%
“…Many anticancer drugs show membrane effects via weak hydrophobic interaction or via electrostatic binding to membrane phospholipids before entering the cytoplasm. In this way, it has been shown that cisplatin can interact with phosphatidylserine to alter the characteristics of the membrane (10).…”
Section: Introductionmentioning
confidence: 99%
“…This spectral parameter has been used widely to monitor various structural and dynamic properties of a wide range of aqueous lipid bilayers and biomembranes. These structural and dynamic properties are: (i) large angle reorientational fluctuations (Auger, 1988;Tupper, 1992;; (ii) interchain packing (Siminovitch, 1987a;Wong, , 1984aWong, , 1989a; (iii) interchain and intrachain configuration distortion (Wong, 1985a); (iv) mechanism for the formation of the lamellar subgel phase (Wong, 1986); (v) interdigitation (Auger, 1988;Siminovitch, 1987bSiminovitch, , 1987cWong 1989b); (vi) interchain interactions (Hubner, 1990; Siminovitch, 1987b;Tupper, 1992); (vii) unsaturation induced changes in molecular configurations in lipid bilayers (Siminovitch, 1987a(Siminovitch, , 1987d; (viii) the effects of anesthetics (Auger, 1988(Auger, , 1990), toxins (Ahmed, 1992;, drugs (Popovic, 1992;Taylor, 1992), alkanes ), cholesterol (Wong, 1989a(Wong, , 1989c, polypeptides (Carrier, 1990), proteins (Gicquaud, 1992;Philp, 1990), fluorescent probes (Chong, 1989(Chong, , 1992, and other exogenous molecules (unpublished work from this laboratory) on the structural and dynamic properties in the bilayer interior of various lipids, and vice versa; (ix) the location and binding sites of these exogenous molecules in lipid bilayers (Ahmed, 1992;Auger, 1988Auger, , 1990Carrier, 1990;Chong, 1989Chong, , 1992; Gicquaud, 1992;Philp, 1990;…”
Section: Introductionmentioning
confidence: 99%